Human‐Centered Design: Developing Evidence to Decision Frameworks and an Interactive Evidence to Decision Tool for Making and Using Decisions and Recommendations in Health Care (Global Challenges 9/2018). Issue 9 (27th September 2018) - Rosenbaum, Sarah E.; Moberg, Jenny; Glenton, Claire; Schünemann, Holger J.; Lewin, Simon; Akl, Elie; Mustafa, Reem A.; Morelli, Angela; Vogel, Joshua P.; Alonso‐Coello, Pablo; Rada, Gabriel; Vásquez, Juan; et al.
Abstract : The Evidence to Decision (EtD) framework is a tool to help groups make systematic, transparent, and adaptable healthcare recommendations or decisions. Through a detailed description of the multi‐stakeholder development of this intervention, Sarah E. Rosenbaum and co‐workers present in article number1700081 important user and stakeholder perspectives relevant for anyone seeking to use or adapt the EtD framework, or who plans to develop similar approaches for supporting groups making evidence‐informed decisions in the context of healthcare or other domains.